IMPLEMENTATION OF THE POLICY TO OPERATE BUS ASSISTANCE OF PATRIOT TRANS IN REALIZING SUSTAINABLE PUBLIC TRANSPORT IN BEKASI CITY WEST JAVA INDONESIA - Bambang Istianto; Wijianto; Sulistyo Sutanto; Nico Djajasinga; Subarto; Paisal Halim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Providing public transport bus assistance to the Bekasi City government is to support an effective urban transport arrangement. Sufficient resources, efficient bus operation institutions, adequate transportation infrastructure, and effective controlhelp the increase in the capacity of public transport services. The purpose of the study is to analyze the extent to which policy implementation has been significant. The theoretical basis used in analyzing policy implementation is the implementation indicator initiated by Edward III. The research method uses qualitative research based on descriptive analysis. Data collection techniques are using documentation techniques and in-depth interviews. Researchers use the triangulation method to analyze data based on information from selected key informants. The results show that the implementation of the Patriot Trans bus operational policy is not yet effective. It is indicated that the routes that have been determined are not suitablefor the needs of the community. The Patriot Trans buses, which are managed bya regional owned enterprise,still can operate with government subsidies, as it is not profitable yet. However, if there are no management changes, the service will stop running. For this reason, the central government needs to harmonize its policies to the technical procedures of the regional governments, such as determining precise and accurate routes, adequate road infrastructure, and competent and professional fleet management. The goal is to guarantee the long-termoperational continuity of the Patriot Trans.